Leveraging aerial and underwater drones and corporate social responsibility to secure Nigeria's oil and gas sector: enhancing crude oil production and strengthening national economic growth - Enisuoh, W.; Pondi, K.; Tangbe, P. (Offshore Technology Conference, 2026)
Nigeria's oil and gas sector remains central to national revenue generation and economic stability, yet its performance has been persistently undermined by crude oil theft, pipeline vandalism, operational inefficiencies, and environmental degradation, particularly in the Niger Delta. These challenges have constrained crude oil production, weakened investor confidence, and limited the sector's contribution to national economic growth. This study examines how integrating aerial and underwater drone technologies with corporate social responsibility (CSR) initiatives can enhance the security, efficiency, and sustainability of Nigeria's oil and gas operations. Table 1 shows Nigeria's crude oil production from 2020 to 2025. These figures combine crude oil and condensate averages where available, and in some markets (like OPEC reporting) exclude condensate, which can affect comparability. The data show an overall downward trend from 2019 peak levels, but gradual stabilization and partial recovery between 2023 and 2025. Using a qualitative analytical approach based on secondary data from academic literature, policy reports, and industry assessments, the study explores the role of aerial drones in monitoring onshore and nearshore pipeline networks, detecting illegal activities, and providing real-time intelligence, as well as the contribution of underwater drones—such as remotely operated vehicles (ROVs)—in inspecting submerged pipelines, detecting leaks, and reducing undetected production losses. The study further situates these technological interventions within a CSR framework that addresses host-community grievances through employment, livelihood support, environmental remediation, and inclusive stakeholder engagement.
Keywords: Corporate social responsibility; Drone; Livelihood; Petroleum industry; Pipeline transport; Production (economics); Revenue; Stakeholder; Sustainability